MERANCANG LEMBAGA KEUANGAN MIKRO SYARIAH YANG TEPAT PADA DESA CIBUNIAN, KECAMATAN PAMIJAHAN, KABUPATEN BOGOR - Kusumaningrum, Ria; Fauziah, Ratu Dinny; Goni, Muhamad Abdul (SAHID DEVELOPMENT JOURNAL : Jurnal Pengabdian Kepada Masyarakat Perbankan Syariah, 2025)
This service aims to establish a sharia microfinance institution in Cibunian Village, Pamijahan District, Bogor Regency, as a solution to increase public access to sharia-based financial services. The background of the service includes the low penetration of formal financial services and the potential of the local economy that has not been fully explored. The service method uses a participatory and inclusive approach, involving the community in the planning, implementation, and evaluation of the program. The results of the service show an increase in people's understanding of Islamic finance and their ability to manage finances effectively. The Islamic microfinance institutions that have been formed have provided sharia savings and microfinance services in accordance with local needs. However, this service faces challenges such as limited resources and community resistance. The conclusion of this service is the need to continue to increase the capacity and support the sustainability of Islamic microfinance institutions in the future.